2021
DOI: 10.1101/2021.08.02.454822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of electrical hybrid-frequency waterbath stunning on the spontaneous electroencephalogram (EEG) and electrocardiogram (ECG) of broilers

Abstract: Concerns about animal welfare and meat quality have encouraged research on new methods for the stunning of broilers during animal slaughter. In this study, the electroencephalogram (EEG) and electrocardiogram (ECG) of broilers were acquired during stunning using an electrical hybrid instead of a single frequency. Considering a square wave with a current of 220 mA and a frequency of 1100 Hz (duty-cycle 50%), the hybrid-frequency waveform is obtained generating pulses at 6600 Hertz in the pulse-width phase. Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…La Vega et al [ 138 ] studied the EEG (EEG electrodes inserted on subcutaneous parts of the occipital scalp of anesthetized birds) and ECG (surface electrode) on broilers stunned by using an electrical hybrid (6600 Hz) in place of a single frequency (220 mA, 1100 Hz, 50% duty cycle). The authors reported better carcass quality and improved animal welfare in the hybrid-frequency system compared to the single-frequency system.…”
Section: Eeg Application In Preslaughter Managementmentioning
confidence: 99%
“…La Vega et al [ 138 ] studied the EEG (EEG electrodes inserted on subcutaneous parts of the occipital scalp of anesthetized birds) and ECG (surface electrode) on broilers stunned by using an electrical hybrid (6600 Hz) in place of a single frequency (220 mA, 1100 Hz, 50% duty cycle). The authors reported better carcass quality and improved animal welfare in the hybrid-frequency system compared to the single-frequency system.…”
Section: Eeg Application In Preslaughter Managementmentioning
confidence: 99%